Surgeon Assessment of a Novel Multi-Resolution Foveated Laparoscope. (December 2022) - Nguyen, Mike; Nabhani, Jamal; Hamilton, Allan; Lee, Sangyoon; Katz, Jeremy; Samakar, Kamran; Ghlandian, Allan; Hua, Hong
Background: We developed a multi-resolution foveated laparoscope (MRFL) to improve situational awareness in laparoscopic surgery. We assessed surgeon objective task performance and subjective attitudes with MRFL when used for box trainer tasks and porcine surgery. Methods: The MRFL simultaneously obtains a wide-angle view and a magnified view. The 2 images are displayed simultaneously. 6 urologists and 2 general surgeons performed box trainer and porcine surgery tasks with the MRFL and a standard laparoscope. Task time, use of display options, and subjective assessments were obtained. Results: Subjectively, surgeons rated situational awareness, depth perception, and instrument interference as comparable between the prototype MRFL and laparoscope for trainer tasks. For porcine surgery, the MRFL was rated as having less interference than the standard laparoscope. The image quality of the MRFL was rated interior to the standard laparoscope. Participants found the different viewing modes useful for different roles and reported that they would likely use the MRFL for conventional laparoscopic and robotic surgery. Objectively, box trainer task time was comparable for 2 of 3 tasks with the remaining task shorter for the standard laparoscope. Porcine nephrectomy and oophorectomy were feasible with the prototype MRFL, although nephrectomy task time was significantly longer than traditional laparoscopy. Conclusions: The MRFL demonstrated feasibility for performing complex surgery. Surgeons had favorable attitudes toward its features and likelihood to use the device if available. Users utilized different view types for different tasks. Longer MRFL task times were attributed to poorer image quality of the prototype.